Immunotargeting and therapy of cancer by advanced multivalence antibody scaffolds. (25th November 2020) - Kafil, Vala; Saei, Amir Ata; Tohidkia, Mohammad Reza; Barar, Jaleh; Omidi, Yadollah
Abstract: Monoclonal antibodies (mAbs) are a swiftly growing class of targeted therapeutics for malignancies. After their first advent, the antibody (Ab) engineering trail has shown an evolutionary trajectory – from the rodent-derived Abs to the chimeric, humanised and fully human Abs with higher efficacy and lower/no immunotoxicity. Despite possessing great clinical potentials, several reports have highlighted that monospecific mAbs, even with high-affinity, often fail to induce sufficient immunologic responses. The full activation of the immune system demands cooperative interactions of immunotherapies with target antigen (Ag) towards functional avidity. Although the monospecific mAbs show affinity to a target Ag, they often fail to render sufficient avidity necessary for the activation of intracellular signalling mechanisms and the provocation of the immune system. Thus, various Ab/non-Ab scaffolds with much greater therapeutic impacts have been engineered based on the adjustment of their affinity and avidity balance. Novel multivalent Ab scaffolds (e.g. MDX-447, MT110, CD20Bi, TF2 and FBTA05) and mimetic Abs (e.g. adnectin, DARPins and ecallantide) offer improved pharmacokinetic and pharmacodynamic properties. Here, we discuss the avidity and multivalency and provide comprehensive insights into advanced Ab scaffolds used for immunotargeting and therapy of cancer.